KARAKTERISTIK ORGANOLEPTIK DAN FISIKOKIMIA PIE UBI UNGU DENGAN CUSTARD PISANG - Muthmainnah, Haura Nada; Delvina, Audrey Diana; Putri, Ade Amelia; Muthmainah, Sayyidah; Ardi, Fakhri Zuhdi; Nurtiana, Winda (Leuit (Journal of Local Food Security), 2025)
Purple sweet potato pie with banana custard is an innovative product that uses purple sweet potato flour as a substitute. This research is an experimental study which aims to determine the acceptability of purple sweet potato pie products with banana custard formulations with different ratios of wheat flour and purple sweet potato flour (F1 (80:20), F2 (70:30), F3 (50:50), and F4 (40:60)). Samples with the best formulation underwent further analysis regarding chemical and physical characteristics. Based on sensory analysis, F3 is the formulation with the highest value for taste and aroma parameters, F4 for color parameters, F2 for texture parameters, and F4 for overall parameters. Formulation 3 (F3) is the selected formulation. Chemical analysis resulted in a water content of 20.15%, ash 1.68%, fat 30.3%, protein 5.05%, carbohydrates 37.74%, crude fiber 5%, and a calorific value of 443.86 kcal/g. Meanwhile, analysis of physical characteristics produces an L* value of 30.04 and a texture of 2.43 N.